AN OVERVIEW AT MACROECONOMIC LEVEL THROUGH ACCOUNTING FIGURES PROVIDED BY THE ECB ASSESSMENT ON EUROZONE BANKING SYSTEM - Olivera Ecaterina OROS; Simona Florina SALISTEANU (Challenges of the Knowledge Society, 2014)
Along with the main macroeconomic indicators, the credit risk indicators became an important leverage in monitoring and evaluating the standard of living at a national level and the country’s economic evolution. These two types of indicators show a strong interconnection, and the correct assessment of the credit risk indicators becomes a must. As a consequence, the central banks and the main regulators in the Europe aria provided for a strict monitoring of such indicators and further on, for constant update of the banking supervisory regulations. In October 2013, the European Central bank (ECB) issued the Note of Comprehensive Assessment that will be carried out during 2014, on the Euro-zone1 banking system. The outcome of the assessment will impact not only the accounting figures of the banking system, but also might change the macroeconomic overview of Euro-zone and the IASB's Conceptual Framework for Financial Reporting.